MENEMUKAN IDEOLOGI WACANA IKLAN LAYANAN MASYARAKAT SURAT KABAR KOMPAS UNTUK MENINGKATKAN KUALITAS LITERASI - Nasir, Muhamad; Puspita, Yenny (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to obtain an in-depth understanding of ideology in the Pepsodent community service ad text in Kompas Newspaper. The research approach is qualitative with critical discourse analysis techniques using Norman Fairclough's critical discourse analysis theory method that combines three dimensions in communication events, namely texts, discourse practices, and socio-cultural practices. Data sources were public service advertisements made by Pepsodent and published in Kompas 2016 Newspaper. The findings of the study showed that there was an attempt to hide the ideology behind the discourse so that the reader did not feel that through the advertisement there was an ideology that was tried to be conveyed by the advertiser through the discourse text. Ideology in the practice of discourse describes factors that influence the production of text, namely, loading or not loading, routine media, and urgency, choosing, and sorting and influencing the views of readers; and the ideology in the consumption of text is the influence of consumption, which is consuming outside information, integrating digital media, following the media agenda, consuming media content according to needs, and relying on mass media information. Ideology in socio-cultural practices illustrates how public service advertisements about dental health are so close to health conditions in Indonesia. In fact, actually the ideology of the company that produces Pepsodent, Unilever is for business purposes.